2011
DOI: 10.1002/bdra.20839
|View full text |Cite
|
Sign up to set email alerts
|

Do foreign‐ and U.S.‐born mothers across racial/ethnic groups have a similar risk profile for selected sociodemographic and periconceptional factors?

Abstract: Significant differences in pregnancy related risk factors during the periconceptional period and throughout pregnancy were observed between maternal nativity groups and across race/ethnicity. Prevention efforts for both prepregnancy and after conception should be designed and delivered according to maternal nativity for each racial/ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In a California-based study of low-income, middle-aged, Mexican-American women those who more strongly identified with Mexican culture had significantly higher odds of meeting the criteria for metabolic syndrome compared to those who more strongly identified with Anglo cultures (Espinosa de Los Monteros, Gallo, Elder, & Talavera, 2008). Two-fold greater odds of gestational diabetes have been reported among foreign-born Hispanic women compared to US-born Hispanic women (Ramadhani et al, 2011) and among immigrant Mexican-American women living in ethnic enclaves compared to immigrant Mexican-American women who were not (Janevic, Borrell, Savitz, Echeverria, & Rundle, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a California-based study of low-income, middle-aged, Mexican-American women those who more strongly identified with Mexican culture had significantly higher odds of meeting the criteria for metabolic syndrome compared to those who more strongly identified with Anglo cultures (Espinosa de Los Monteros, Gallo, Elder, & Talavera, 2008). Two-fold greater odds of gestational diabetes have been reported among foreign-born Hispanic women compared to US-born Hispanic women (Ramadhani et al, 2011) and among immigrant Mexican-American women living in ethnic enclaves compared to immigrant Mexican-American women who were not (Janevic, Borrell, Savitz, Echeverria, & Rundle, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have suggested that acculturation is significantly associated with cardiometabolic health in Mexican-American women. Proxies of lower acculturation (i.e., being Mexico-born, shorter duration of US residence, or use of Spanish as a primary language at home) have been associated with greater prevalence of negative cardiometabolic indicators among Mexican-American women, particularly diabetes (Dinwiddie, Zambrana, & Garza, 2014), abdominal obesity (Sundquist & Winkleby, 2000), and gestational diabetes (Ramadhani et al, 2011). Conversely, longitudinal evidence shows that among Mexican-American immigrants diabetes risk increases with longer residence in the US (Anderson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, most of these births occurred to Hispanic women, the majority of whom were from Mexico (146,173). In New York City, Savitz et al (172) found that foreign nativity increased the odds for GDM in women of most racial/ethnic groups and subgroups of Hispanics, as well as among Chinese and Filipinos.…”
Section: Country Of Nativitymentioning
confidence: 99%
“…Foreign-born women also have a greater prevalence of GDM than women born in the United States, and this disparity has increased from the 1990s to early 2000s (146,172,173). In two studies, most of these births occurred to Hispanic women, the majority of whom were from Mexico (146,173).…”
Section: Country Of Nativitymentioning
confidence: 99%
“…2 In two separate cohorts, maternal prepregnancy body mass index (BMI; calculated as kg/ m 2 ) were nearly identical: 5% of women were underweight, 53% to 55% were normal weight, 22% to 23% were overweight, and 18% to 19% were obese. 3,4 Accordingly, approximately one in five women enter pregnancy overweight, whereas one in six women enter pregnancy with obesity. These data point to a potential vicious cycle of obesity that has been described previously.…”
mentioning
confidence: 99%